Key concepts in economic geography - Aoyama, Yuko.; Murphy, James T. (Associate professor of geography); Hanson, Susan, 1943-; Sage eBooks (Los Angeles : SAGE, 2011)
Organized around 20 short essays, 'Key Concepts in Economic Geography' provides a cutting edge introduction to the central concepts that define contemporary research in economic geography.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Economic geography; Electronic books